Modern electronic communication - Miller, Gary M.; Beasley, Jeffrey S. (New Delhi : Prentice Hall of India, 2006)
Engineering
Keywords: Electronic communication; Modern electronic; Amplitude modulation; LC circuits; Single-sideband communication; Frequency modulation; Transmission; Digital communication; Network communication; Transmission line; Wave papagation; Antennas; Microwaves and lasers; Television; Fibre optics